Arthroscopic-Assisted Reduction and Internal Fixation With Bone Allograft in Closed Tibial Plateau Fracture - Danaithep Limskul, M.D.; Nawit Yoosuksomboon, M.D.; Napatpong Thamrongskulsiri, M.D.; Thun Itthipanichpong, M.D.; Thanathep Tanpowpong, M.D.; Somsak Kuptniratsaikul, M.D. (Arthroscopy Techniques)
Tibial plateau fractures, though rare, are critical due to their impact on weightbearing and joint function. The gold standard for surgical treatment is open reduction and internal fixation (ORIF), aiming to restore the tibial plateau’s anatomy and address any concurrent injuries. However, ORIF involves extensive soft tissue dissection, posing risks such as infections, neurovascular injury, and long-term joint stiffness. This Technical Note presents an arthroscopic-assisted approach for the reduction and internal fixation of a Schatzker II tibial plateau fracture. The procedure involved minimal incisions, direct arthroscopic visualization, and the use of bone allograft to support the elevated plateau. This method offers several advantages over traditional ORIF, including reduced soft tissue dissection, decreased risk of complications, and improved precision in anatomic reduction. The technique also facilitates the diagnosis and treatment of associated intra-articular injuries, potentially leading to better functional outcomes and faster recovery.